PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI TENDIK UNIVERSITAS MA CHUNG - Basory, Hartomy Akbar; Broto, Felik Sad Windu Wisnu; Rossach, Michael Marshal Bintang (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
To substantiate the performance of Ma Chung University educators, evidence is required, this study aims to ascertain and examine the impact of work discipline and work motivation on the performance of educators employed at Ma Chung University. The study population consisted of a total of 85 personnel who were educators at Ma Chung University. The sample size in this study consisted of 46 educational personnel who were distributed throughout multiple regions. Utilising multiple linear regression for data analysis approaches. The findings indicated that both work discipline and work motivation variables had a beneficial but statistically negligible impact on the performance of employees at Ma Chung University. Partial tests have shown that work discipline has a positive but minor impact on the performance of employees at Ma Chung University. On the other hand, work motivation has a favourable and large impact on the performance of these employees.